Algorithms and Convergence Theorems for Mixed Equilibrium Problems in Hilbert Spaces. (11th June 2019) - Chih-Sheng, Chuang
Abstract: In this article, we study mixed equilibrium problems, and present algorithms and convergence theorems for the proposed algorithms, like proximal gradient method, Tikhonov regularization method, Mann's type method, conjugate gradient method. As application, we study minimization problems.